Maintenance mechanisms of tree diversity in Mexican coniferous forests - Sánchez-Presa, Libertad (2020)
This project aims to understand how the diversity of conifers in Mexico been generated and the mechanisms through which it is maintained. Specifically I ask how conifer diversity is influenced by environmental drivers, how the distribution of conifers in Mexico is influenced by environmental stressors and the extent to which the traits exhibit phylogenetic conservatism and how beta diversity patterns are shaped by geographic and environmental distance. In order to answer this questions I used data from the Forest and Soils National Inventory of the Mexican Forestry Commission, a database of conifer traits, environmental data and a phylogeny of Mexican conifers. The results show that environmental variables influence species richness and functional diversity to varying extents. There was however a consistent effect of the interaction of temperature and precipitation on both species richness and functional diversity. I found that temperature and precipitation seasonality do not necessarily constrain species richness or functional diversity. Annual precipitation was showed to be the environmental variable that best explains the geographical patterns of conifer traits in Mexico. Overall, the functional traits exhibited phylogenetic signal consistent with niche conservatism, with several functional traits showing dependency with climate variables even after correcting for phylogenetic relatedness. Beta diversity across Mexico is mostly influenced by environmental distance. However, both geographic and environmental distance play important roles in shaping species, functional and phylogenetic beta diversities.